Analysis of The Legal Basis of Non-Bank Financial Institutions in Conventional and Sharia Cooperatives - Shafa Haura Asma Hamidah; Yoppi Harya Fahassanta; Nariza Isandra; Anisah Maharani Putri Werdani; Wildan Fattahur Rozaq; Nur Rudin Dian Saputra (Proceeding International Conference Restructuring and Transforming Law, 2023)
Financial institutions play an important role in the finances of a State. Financial institutions in Indonesia are divided into two, Bank Financial Institutions and Non-Bank Financial Institutions. Cooperatives as financial institutions function in helping the Indonesian economy, so based on this, the applicable bookkeeping must be analyzed so as not to have a negative impact on the Indonesian economy itself in the future. This research was carried out using the literature study research method which was sourced from existing literature. The analysis technique used uses data triagulation techniques, where the data obtained later aims to analyze the law that forms the basis of conventional and Islamic cooperative activities. In the research, it was found that there are laws that regulate the activities of cooperatives in Indonesia, both conventional cooperatives and sharia cooperatives.